ANALISIS EKONOMI WILAYAH DAN INTRA WILAYAH KABUPATEN MUSIRAWAS UTARA SEBAGAI DAERAH PENGHASIL KELAPA SAWIT DI PROVINSI SUMATERA SELATAN: - - Utomo, Rohadi; Siddiq, Amar (Jurnal AGRISEP, 2024)
This research aimed to identify the key economic sectors that could uplift Musi Rawas Utara Regency from its underdeveloped status within Sumatra Selatan Province. The study employed a descriptive-analytical approach, which included analyzing primary sectors using the Location Quotient (LQ) method, determining leading sectors through Shift Share analysis, and assessing the contribution of the primary highest-value industry using Intra-Regional analysis. Among the 17 sectors contributing to the Gross Regional Domestic Product (GRDP), five were identified as primary sectors in Musi Rawas Utara Regency, with a significant dominance of the Agriculture, Forestry, and Fisheries sectors. However, Shift Share analysis revealed two leading sectors: education and health services with social activities. We identified seven potential sectors: industrial, infrastructure, and developing sectors. Developing sectors include agriculture, forestry, fisheries, mining and quarrying, and education. Meanwhile, five sectors were considered underdeveloped: the processing industry, construction, transportation and trade, financial services and insurance, government administration, defense, and taxpayer social security. LQ analysis emphasized that the agricultural and forestry sector is the primary sector in Musi Rawas Utara Regency, with palm oil production being a vital contributor. For the development of palm oil, Nibung and Karang Dapo districts require particular attention. Given Musi Rawas Utara Regency's disadvantaged status, optimizing agricultural sector development is crucial. By focusing on this sector, the region can enhance its economic performance, ultimately aiming to overcome its underdeveloped status and improve its financial outlook.